Hijacking the BAF complex: the mechanistic interplay of ARID1A and EWS::FLI1 in Ewing sarcoma - Erich J. Sohn; David S. Libich (Molecular Oncology)
Ewing sarcoma, an aggressive pediatric cancer, is driven by the EWS::FLI1 fusion protein, which disrupts gene expression by hijacking the BAF chromatin remodeling complex. Central to this mechanism is the formation of biomolecular condensates, mediated by the prion‐like domains (PrLDs) of EWS and ARID1A, a core BAF subunit. ARID1A serves as a critical interface between EWS::FLI1 and the BAF complex, with its condensate‐forming ability essential for the aberrant gene expression that drives tumor growth. The loss of condensate‐competent ARID1A significantly impairs tumor progression, identifying it as a potential therapeutic target. However, targeting condensate formation is challenging due to the transient nature of the interactions involved, complicating the development of effective inhibitors. This work underscores the importance of further investigation into therapeutic strategies aimed at disrupting condensate formation in Ewing sarcoma and other related malignancies.